2016
DOI: 10.1002/bse.1918
|View full text |Cite
|
Sign up to set email alerts
|

Gender Diversity on Boards and Firms’ Environmental Policy

Abstract: This paper tests the relationship between gender diversity on boards and firms’ environmental policy. Based on prior research, we predict that gender diversity on boards of directors should have a positive relationship with firms’ environmental policy. Moreover, firm character in terms of pollution creation likelihood moderates the relationship between gender diversity on boards and firms’ environmental policy. Analyzing data from 865 publicly listed firms in the United States, we found direct and significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
160
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(172 citation statements)
references
References 56 publications
11
160
0
1
Order By: Relevance
“…Thus, Hypothesis is supported. Our result illustrated in Figure is consistent with the findings in Li et al () who also found an industry effect. However, compared with Li et al (), we use a much larger sample size (4,872 firm‐year observations vs. 865 observations), more recent data (2009–2015 vs. 2010), and a different dependent variable (environmental performance vs. environmental policy).…”
Section: Resultssupporting
confidence: 93%
“…Thus, Hypothesis is supported. Our result illustrated in Figure is consistent with the findings in Li et al () who also found an industry effect. However, compared with Li et al (), we use a much larger sample size (4,872 firm‐year observations vs. 865 observations), more recent data (2009–2015 vs. 2010), and a different dependent variable (environmental performance vs. environmental policy).…”
Section: Resultssupporting
confidence: 93%
“…First, most studies have been conducted in the context of developed countries [24]. Therefore, it is unclear whether the conclusions from the previous studies with samples from developed countries are still supported in developing countries.…”
Section: Introductionmentioning
confidence: 93%
“…Independent directors are more likely to highlight the importance of CSR concerns [62]. We also control the industry of the firm samples based on the three-digit industry code used by China Securities Regulatory Commission (CSRC) as the industry has been recognized as a significant factor influencing the firms' CSR performance [24]. The summary of the measurement for each variable has been presented in Table 2.…”
Section: Measurementmentioning
confidence: 99%
“…Moreover, sustainability expertise, for example, in the form of a sustainability committee, may also positively affect SRQ (Cucari, Esposito De Falco, & Orlando, 2018;Hahn & Kühnen, 2013;Helfaya & Moussa, 2017;Liao et al, 2015;Michelon & Parbonetti, 2012). Diversity of board members is assumed to add broad and heterogeneous perspectives to the boards' decision-making processes, which may improve CSP and enhance firms' ability to meet the needs of broader stakeholder groups (Landry, Bernardi, & Bosco, 2016;Li et al, 2017;Liao et al, 2015;Prado-Lorenzo & Garcia-Sanchez, 2010;Rao & Tilt, 2016). Diversity of board members is assumed to add broad and heterogeneous perspectives to the boards' decision-making processes, which may improve CSP and enhance firms' ability to meet the needs of broader stakeholder groups (Landry, Bernardi, & Bosco, 2016;Li et al, 2017;Liao et al, 2015;Prado-Lorenzo & Garcia-Sanchez, 2010;Rao & Tilt, 2016).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%